Economic evaluation of a community based exercise programme to prevent falls. Issue 8 (1st August 2001) - Robertson, M Clare; Devlin, Nancy; Scuffham, Paul; Gardner, Melinda M; Buchner, David M; Campbell, A John
Abstract : OBJECTIVE: To assess the incremental costs and cost effectiveness of implementing a home based muscle strengthening and balance retraining programme that reduced falls and injuries in older women. DESIGN: An economic evaluation carried out within a randomised controlled trial with two years of follow up. Participants were individually prescribed an exercise programme (exercise group, n=116) or received usual care and social visits (control group, n=117). SETTING: 17 general practices in Dunedin, New Zealand. PARTICIPANTS: Women aged 80 years and older living in the community and invited by their general practitioner to take part. MAIN OUTCOME MEASURES: Number of falls and injuries related to falls, costs of implementing the intervention, healthcare service costs resulting from falls and total healthcare service costs during the trial. Cost effectiveness was measured as the incremental cost of implementing the exercise programme per fall event prevented. MAIN RESULTS: 27% of total hospital costs during the trial were related to falls. However, there were no significant differences in health service costs between the two groups. Implementing the exercise programme for one and two years respectively cost $314 and $265 (1995 New Zealand dollars) per fall prevented, and $457 and $426 per fall resulting in a moderate or serious injury prevented. CONCLUSIONS: The costs resulting from falls make up a substantial proportion of the hospital costs for older people. Despite a reduction in falls as a result of this home exercise programme there was no significant reduction in healthcare costs. However, the results reported will provide information on the cost effectiveness of the programme for those making decisions on falls prevention strategies.